2016
DOI: 10.1002/ente.201600086
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Characteristics of Ignition during Microwave Drying of Lignite

Abstract: The spontaneous combustion of lignite during microwave drying was evaluated with the focus on the effects of, for example, microwave power and output mode, the final temperature of the samples, and the oxygen content of the drying atmosphere on the moisture contents corresponding to the ignition (IMCs). This empirical study was performed using a laboratory‐scale microwave oven. The lowest IMCs and the optimal drying effect of lignite were achieved using a power level of 60 W g−1, final surface temperature of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…When the applied microwave power level is 800 W, an obviously constant rate period appears, which is similar to the former researchers' experimental results. Song et al [48] found that the constant rate period were discovered under 700 W, while it disappeared at 800 W. This can be explained by a great deal of heat energy generation and higher pressure difference at microwave power levels beyond 700 W, leading to the increasing drying rate and the final temperature of lignite reaching 181 °C, as can be observed in Figure 3a.…”
Section: The Effect Of Microwave Power Levels During Microwave Dryingmentioning
confidence: 87%
“…When the applied microwave power level is 800 W, an obviously constant rate period appears, which is similar to the former researchers' experimental results. Song et al [48] found that the constant rate period were discovered under 700 W, while it disappeared at 800 W. This can be explained by a great deal of heat energy generation and higher pressure difference at microwave power levels beyond 700 W, leading to the increasing drying rate and the final temperature of lignite reaching 181 °C, as can be observed in Figure 3a.…”
Section: The Effect Of Microwave Power Levels During Microwave Dryingmentioning
confidence: 87%